2014
DOI: 10.1103/physics.7.59
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Imaging of Superresolution

Abstract: N00N states-maximally path-entangled states of N photons-exhibit spatial interference patterns sharper than any classical interference pattern. This is known as superresolution. However, even given perfectly efficient number-resolving detectors, the detection efficiency of all previous measurements of such interference would decrease exponentially with the number of photons in the N00N state, often leading to the conclusion that N00N states are unsuitable for spatial measurements. A technique known as the "opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However it was suggested that to detect such interference patterns one could simply proceed to optical centroid measurements of the N detected photons of the NOON state [142]. This method was later implemented [146] for 2 photon NOON states and for up to 4 photon NOON states [147,148]. Finally, it has been shown that multiphoton interference with independent single photon light sources can also lead to a similar super-resolved interference pattern [149], without using path entangled states.…”
Section: Superresolution In Quantum Imagingmentioning
confidence: 99%
“…However it was suggested that to detect such interference patterns one could simply proceed to optical centroid measurements of the N detected photons of the NOON state [142]. This method was later implemented [146] for 2 photon NOON states and for up to 4 photon NOON states [147,148]. Finally, it has been shown that multiphoton interference with independent single photon light sources can also lead to a similar super-resolved interference pattern [149], without using path entangled states.…”
Section: Superresolution In Quantum Imagingmentioning
confidence: 99%